Partisipasi Politik Perempuan Perspektif Hukum Islam - Warjiyati, Sri (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2016)
Abstract: This article discusses political participation of women from the perspective of Islamic law.Â In paricular, it will highlights a women political organization called KPPI (Kaukus Politik Perempuan Indonesia or Indonesian political women caucus).Â There are obstacles and challenges for improving women political participation due to personal, internal and external issues. For personal issues, the political awareness for women is relatively low which needs improvement. For internal perspective, not all available political parties gives space and opportunity for women political development, whereas externally, the improvement of women political participation is so limited that they do not participate in politics and do politics correctly. Islam provides equal opportunity for men and women in politics. This can be seen in many sex-neutral injunctions in the Holy Qurâan which commands amar maâruf nahi munkar (promote the good and prevent the evil).Â This command encompasses all aspects of life, including politics and state issues. Women are also responsible in this respect. Based on that, Islam provide ground for women to actively in politics.Keywords: women political participation, Islamic LawÂ Abstrak: Artikel ini membahas tentang partisipasi politik perempuan perspektif hukum Islam. Partisipasi politik perempuan di Indonesia tergabung pada Kaukus Politik Perempuan Indonesia (KPPI). Terdapat berbagai hambatan dan tantangan dalam upaya peningkatan partisipasi politik perempuan, baik secara personal, internal maupun eksternal. Secara personal, kesadaran berpolitik bagi perempuan relatif masih rendah, sehingga perlu ditingkatkan. Dari sisi internal, belum semua partai memberikan ruang dan kesempatan bagi pengembangan politik perempuan, sedangkan secara eksternal, peningkatan partisipasi politik perempuan masih mengalami banyak keterbatasan, sehingga perempuan masih relatif rendah untuk masuk dalam politik dan berpolitik secara benar. Islam memberikan kesempatan kepada kaum perempuan yang berkecimpung dalam kegiatan politik, ini bisa terlihat pada banyak ayat dalam al-Qurâan yang memerintahkan amar maâruf nahi munkar. Ini berlaku untuk segala macam kegiatan, tidak terkecuali dalam bidang politik dan kenegaraan. Perempuan juga turut bertanggungjawab dalam hal ini. Berdasarkan hal tersebut, maka perempuan dalam Islam juga memiliki hak untuk berpartisipasi dalam politik.Kata Kunci: partisipasi, politik, perempuan, hukum Islam.